Effect of different drying techniques on the nutritional values of oyster mushroom (pleurotus sajor-caju) - Aishah, M.S.; Wan Rosli, W.I. (Universiti Kebangsaan Malaysia, 2013)
Mushrooms are basically fungi, which have fleshy and spore-bearing fruiting body. This family of fungi literally has thousands of varieties of mushroom throughout the world. Oyster mushrooms are uniquely distinctive and they do look like oysters. Drying these mushroom confer a stabilizing property to it and then can be stored for a longer period. The nutritional values of the dried oyster mushroom with different drying techniques were thus determined. There were three different drying techniques used. These include low heat air blow (LHAB, AnjaadTM), sun drying (SD) and gas laboratory oven (LO) drying. All three samples were analyzed for beta-glucan content, water activity, colour, proximate analysis and dietary fibre concentration. The result showrd that LHAB method confers the lowest water activity compared with the other two drying methods. It also has the lowest colour measurement for brightness. Mushroom samples dried by LHAB techniques contain the highest concentration of both fat and carbohydrate compared with the other two methods. Besides, SD method confers the highest beta-glucan content. On the other hand, dietary fibres observed in LO dried samples contain the highest fibre content among the three drying treatments. In conclusion, LHAB method is recommended in reducing water activity and increasing proximate contents while both SD and LO are good in preserving beta-glucan and dietary fibre contents, respectively.